Perkembangan dan Peran Nederlands Koloniaal Bestuur dalam Penyelenggaraan Perpustakaan di Hindia-Belanda Awal Abad XX - Putra, Purwanto (Perpustakaan Nasional, 2024)
This article examines the role of the government in managing libraries in the Dutch East Indies and the development of libraries from 1887 to 1914. The main focus is on official reports and related data from that period, including library management, public interest in library services, and the evolution of these services in a colonial context. The goal of writing the history of library management in the Dutch East Indies is to offer a deeper understanding of the root causes, the development of information services, and the government's role in shaping literacy in the past. This research uses a historical method based on various primary sources from digital databases, collected between July and August 2024. The methodology includes topic selection, source collection and verification, data interpretation, and historiography, ensuring a systematic approach based on credible sources. Primary sources come from the Delpher database and the digital collections of Leiden University. Delpher was used to explore Dutch newspapers, books, and magazines, while Leiden's digital archives provided relevant documents. The findings show that while the government of the Dutch East Indies was involved in library management, its support was mainly limited to administrative oversight and basic regulation. Challenges included inadequate funding and a lack of trained librarians, which affected the quality of services and collection management. A significant disparity in support for libraries between the Netherlands and the Dutch East Indies was evident in the early 20th century.